Alpha-lipoic acid (ALA) supplementation effect on glycemic and inflammatory biomarkers: A Systematic Review and meta- analysis. (August 2019) - Rahimlou, Mehran; Asadi, Maryam; Banaei Jahromi, Nasrin; Mansoori, Anahita
Summary: Background & aims: Several randomized clinical trials (RCTs) have investigated the effect of Alpha - Lipoic Acid (ALA) supplementation on metabolic parameters, with conflicting results. Therefore, the present study assessed the effect of ALA on some glycemic and inflammatory parameters. Methods: A comprehensive literature search was conducted up from inception to July 2018 on PubMed, Scopus, Cochrane databases, Google Scholar, ProQuest, Web of Science, and Embase. From among eligible trials, 41 articles were selected for the meta-analysis. Two reviewers independently assessed the risk of bias and extracted data from the included studies. Meta-analyses using the random-effects model were performed to analyze the data. Results: Based on the Cochrane risk of bias tool, 19 articles had a good quality, 16 trials had a poor quality and 6 trials had a fair quality. The results demonstrated the significant effect of ALA on Fasting Blood Sugar (FBS) (weighted mean difference (WMD)) = –6.57, 95% confidence interval (CI: −11.91 to –1.23, P = 0.016), Hemoglobin A1c (HbA1c) (WMD = –0.35, 95% CI: –0.55 to –0.15, P = 0.004), Tumor Necrosis Factor Alpha (TNF-α) (WMD = −1.57, 95% CI: –2.29 to –0.85, P < 0.05), Interleukin 6 levels (IL-6) (WMD = –1.15, 95% CI: –1.58 to –0.72, P < 0.001), and C-reactive protein (CRP) (WMD = –0.31, 95% CI: –0.47 to −0.16, P > 0.001). No effect was detected for ALA on insulin and the homeostatic model assessment of insulin resistance (HOMA-IR). Conclusions: These findings suggest that ALA is a viable supplement to improve some of the glycemic and inflammatory biomarkers.